Factors Contributing to Rising Diabetes Cases in Indonesia: Insights from the 2023 Indonesian Health Survey - S.K.M., M. Epid., Mivtahurrahimah; Sevtiyani, Imaniar (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: The 2023 Indonesian Health Survey (SKI) revealed an increase in diabetes mellitus (DM) prevalence among individuals aged ≥15 years from 2.0% in 2018 to 2.2% in 2023, potentially linked to post-COVID-19 lifestyle changes. This study explored factors contributing to the rising diabetes cases in Indonesia using 2023 SKI data.Methods: This cross-sectional study utilized aggregate data from the 2023 SKI, collected between March and May 2025. The study selected 34,500 census blocks using proportional stratified sampling. Data collection involved interviews and physical examinations. Spearman's correlation and linear regression identified diabetes-related risk factors.Result: Positive correlations were found between DM and daily smoking, former smoking, high-fat food consumption, body weight monitoring, telemedicine use, and obesity. Negative correlations were observed for occasional smoking exposure, tobacco use, sweet food consumption, and normal nutritional status. Physical activity showed no significant association. Multivariate analysis revealed that individuals with blood pressure checks less than once a year had an 8.63-fold higher DM risk. Telemedicine use, low-frequency starchy tuber intake, and BPJS PBI membership were associated with increased risk, while nut consumption (1–6 times/week) reduced the risk by 26%.Conclusion : Behavioral and healthcare access factors significantly influenced diabetes risk. Smoking, unhealthy diet, and limited health monitoring increased this risk. Further research using individual-level data is recommended to better understand these associations and inform targeted interventions.Keywords: Diabetes prevalence, Risk factors, Indonesian Health Survey 2023, Lifestyle Behaviors, Healthcare access.